Outcomes of precut sphincterotomy techniques in cases of difficult biliary access - Rejeski, Jared (Frontline Gastroenterol, 2020)
GOALS: Our study aims to define success and complication rates of precut sphincterotomy with the needle-knife and transpancreatic papillary septotomy (TPS) techniques as experienced at a single, high-volume endoscopy centre. BACKGROUND: Complication rates rise with increasing number of failed attempts at biliary cannulation; therefore, early precut sphincterotomy (PS) has been recommended. Selecting the ideal method for PS can be challenging and there is a paucity of data to help guide this decision. STUDY: We performed a retrospective analysis over 37 months of endoscopic retrograde cholangiopancreatography (ERCP) experience at a single institution. We identified all ERCPs performed and stratified based on the presence of PS; if PS occurred, a thorough chart review was performed to identify success and complication rates. Patients received guideline-driven management for post-ERCP pancreatitis including rectal indomethacin and pancreatic duct stenting when appropriate. RESULTS: We identified 1808 ERCP procedures performed during this time. Successful biliary cannulation was achieved in 1748 cases, yielding a success rate of 96.7% (Grades I–IV ERCP difficulty/complexity). PS was required in 232 cases (12.8%); we identified 88 TPS cases and 114 needle-knife precut sphincterotomy (NKPS) cases. Complications following PS procedures occurred in 9.1% of TPS patients and 11.4% of NKPS patients. Success rates for TPS and NKPS were 97.7% and 81.6%, respectively—a statistically significant difference (p<0.001). CONCLUSION: This data supports TPS as a safe and effective option for biliary access in difficult cannulation settings when performed by experienced advanced endoscopists.